Narratives of Indonesian pre-service English teachers’ agency in international teaching practicum - Nadya Loemongga; Willy Prasetya (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Teacher agency is a central component that highly influences a teacher’s perspective and practices. Despite extensive research on teacher agency among pre-service teachers, limited understanding of teacher agency within existing structures and system in education particularly in International Teaching Practicum (ITP). The present study explored narratives from two pre-service English teachers in terms of teacher agency. One participant had conducted ITP in Vietnam, while the other was in the Philippines. The data were collected through a series of semi-structured interviews. Through a thematic analysis, the results of this study indicated that the two participants transformed their teacher agency as they practiced it under the influence of various aspects, including sociocultural differences, teaching challenges, and assistance from other teachers. Teachers can transform their agency by embracing the diverse cultural backgrounds of their students and incorporating culturally relevant teaching strategies. When it comes to teaching challenges, teachers can collaborate with their colleagues to share ideas, resources, and strategies. This collaboration can be through professional learning communities, mentorship programs, or even informal conversations. Seeking assistance from other teachers can provide valuable support and fresh perspectives. It pertains entirely to building a strong network of educators who can inspire and empower each other. This study provides empirical evidence of teacher agency in ITP that may serve as a starting point for further research in the same context.